Treatment of Mandibular Fractures (International Journal of Medical and Surgical Sciences, 2016)
Treatment of mandibular fractures and their sequelae are difficult to resolve in the maxillofacial surgery field, their components cause that reduction must not only be anatomic, but functional as well. The aim of this article is to present a review about actual knowledge in mandibular fracture treatment and report a case of mandibular trauma. The treatment of these fractures has been changing through the years; the new technologies achieve better reduction with the osteosynthesis systems, which results in reduced approaches and lesser morbidity. Presently, titanium plates systems like mini-plates, reconstruction plates or blocking plates offer excellent results in high energy traumas through anatomic and stable reductions. The technology of 3D reconstruction systems and intra-operatory CT accomplishes better results in trauma treatment.
Keywords: Mandibular Fracture; Osteosynthesis; Squelae